Design, Synthesis and In Vitro Investigation of Cabozantinib-Based PROTACs to Target c-Met Kinase - Anastasia A. Sachkova; Daria V. Andreeva; Alexander S. Tikhomirov; Alexander M. Scherbakov; Diana I. Salnikova; Danila V. Sorokin; Fedor B. Bogdanov; Yulia D. Rysina; Andrey E. Shchekotikhin; Ekaterina S. Shchegravina; Alexey Yu. Fedorov (MDPI AG, 2022)
(1) Background: This investigation aimed at developing a series of c-Met-targeting cabozantinib-based PROTACs. (2) Methods: Purification of intermediate and target compounds was performed using column chromatography, in vitro antiproliferation activity was measured using a standard MTT assay and a c-Met degradation assay was performed via the immunoblotting technique. (3) Results: Several compounds exhibited antiproliferative activity towards different cell lines of breast cancer (T47D, MDA-MB-231, SKBR3, HCC1954 and MCF7) at the same level as parent cabozantinib and 7-demethyl cabozantinib. Two target conjugates, bearing a VHL-ligand as an E3-ligase binding moiety and glycol-based linkers, exhibited the effective inhibition of c-Met phosphorylation and an ability to decrease the level of c-Met in HCC1954 cells at micromolar concentrations. (4) Conclusions: Two compounds exhibit c-Met inhibition activity in the nanomolar range and can be considered as PROTAC molecules due to their ability to decrease the total level of c-Met in HCC1954 cells. The structures of the offered compounds can be used as starting points for further evaluation of cabozantinib-based PROTACs.